2019
DOI: 10.1177/0950017019841552
|View full text |Cite
|
Sign up to set email alerts
|

The Rise in Pay for Performance Among Higher Managerial and Professional Occupations in Britain: Eroding or Enhancing the Service Relationship?

Abstract: Higher managerial and professional occupations are now the most incentivized occupational class in Britain. It is not yet known whether the rise in pay for performance (PFP) signifies an erosion or enhancement in the ‘service relationship’ that purportedly characterizes these occupations. Taking an occupational class perspective, this article investigates the implications of the rise in PFP for the employment relationship and conditions of work across the occupational structure using two nationally representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Along this line, one element of potential concern in our results is the positive association between computer use and productivity PFP. Although individual contingent pay schemes have been found to have positive effects on attitudes such as job satisfaction and commitment (Ogbonnaya et al., 2017), they also show negative effects on employee welfare through greater work intensification and job strain (Ogbonnaya et al., 2017; Williams et al., 2020). Therefore, in the adoption of PFP schemes associated with increased computer use, attention should be paid to design issues such as the definition of standards and the pay rate that guarantee a balance between the effort provided by the worker, the rewards received and the resources assigned to perform their tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along this line, one element of potential concern in our results is the positive association between computer use and productivity PFP. Although individual contingent pay schemes have been found to have positive effects on attitudes such as job satisfaction and commitment (Ogbonnaya et al., 2017), they also show negative effects on employee welfare through greater work intensification and job strain (Ogbonnaya et al., 2017; Williams et al., 2020). Therefore, in the adoption of PFP schemes associated with increased computer use, attention should be paid to design issues such as the definition of standards and the pay rate that guarantee a balance between the effort provided by the worker, the rewards received and the resources assigned to perform their tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, one element of potential concern in our results is the positive association between computer use and productivity PFP. Although individual contingent pay schemes have been found to have positive effects on attitudes such as job satisfaction and commitment (Ogbonnaya et al, 2017), they also show negative effects on employee welfare through greater work intensification and job strain (Ogbonnaya et al, 2017;Williams et al, 2020).…”
Section: Implications For Practicementioning
confidence: 99%
“…More generally, occupational differentiation in PFP within organizations may result in unhelpful negative attitudes between groups that are treated differently (Marescaux et al , 2013) as employees' equity concerns may be more closely tied to their organizational than wider professional environment. Finally, it has been established that PFP jobs pay more (Williams et al , 2020). Given our research finds that PFP is more likely to be found in jobs in occupations where monitoring difficulty and requisite human asset specificity is high, which also are generally higher-paying occupations (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A second dimension of inequality in work highlighted by the literature is the nature of pay policies. The growth of human resource management led to a sharp rise in use of individual performance payment systems in the 1990s (McGovern et al, 2007; Williams et al, 2019), which reinforce inequalities between occupational classes. Performance‐related pay readily raises issues about fairness, given that supervisory judgements on relative performance may be difficult justify.…”
Section: Theoretical Issues and Research Questionsmentioning
confidence: 99%
“…Performance‐related pay readily raises issues about fairness, given that supervisory judgements on relative performance may be difficult justify. The benefits of performance‐related pay for overall pay levels, however, also differ substantially between occupational classes: while providing a bonus on top of base earnings for managers and professionals, it partially substitutes for base earnings in less skilled occupational classes, thereby increasing risks of pay loss (Williams et al, 2019).…”
Section: Theoretical Issues and Research Questionsmentioning
confidence: 99%